Use and inappropriate use of proton pump inhibitors in hospitalized patients - Gupta, Yadvendra; Bhandari, Sudhir; Govil, Anurag; Gupta, Rahul; Goyal, Jaswant; Goyal, Barkha; Chandalia, Saloni (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The discovery of Helicobacter pylori infection in etiology of peptic ulcer disease and proton pump inhibitors (PPI) in management of upper gastrointestinal diseases had been the milestones in medical science. PPI are currently being both overused and misused. In countries like India, where over 500 branded formulations of PPI are available, probability of misuse and abuse increases exponentially. The aim of the study was to find out inappropriate use of PPI, among hospitalized patients. Methods: In order to find answer to the research question a cross sectional study was conducted in indoor patient of a tertiary care private hospital at Jaipur, Rajasthan. Patients of either sex, aged 18 years or above belonging to rural and urban communities were participating in study. The sample size was 500. Results: It was noted that Inappropriate PPI use was observed in most of the hospital admitted patients (78%). Most common diagnosis among inappropriate PPI use was dengue fever (due to increased number of dengue cases during study period), followed by cerebrovascular accidents and urinary tract infection. Most common indication for appropriate PPI use was stress ulcer prophylaxis, again in dengue case (due to cardinal manifestation of thrombocytopenia). Conclusions: Almost all patients were once prescribed PPI after admission and discharged on PPI (99.2%). Thus, we recommend evidence-based prescription of PPI, to reduce side effects and excess cost.